PENGEMBANGAN MATERI AJAR TEKS CERPEN BERBANTUAN VIDEO MULTIMEDIA PADA SISWA KELAS XI MAS AL WASHLIYAH MEDAN - Halimatussakdiah (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2023)
This study intends to analyze the process, form, and feasibility of developing teaching materials for short story texts using multimedia video assistance for grade XI students of MAS AL WASHLIYAH using the 4D model. However, this study is limited to the development stage due to limited time and conditions. The validation stage involved material and design expert lecturers to evaluate the feasibility of the material and design. Data collection techniques used questionnaires and instruments. The data were analyzed using quantitative descriptive analysis. The results showed that the product of the development of short story text teaching materials using multimedia video assistance obtained research results with "Very Good" criteria with an average of 87.8%. The evaluation results from material experts showed 90% with the criteria of "Good" and the results from media experts amounted to 85.6% with the criteria of "Very Good". Therefore, the teaching materials are considered suitable for use as supporting teaching materials in the learning process.